Self - "Sivananda, Swami" (Tehri-Garhwal, 1995)
Swami Sivananda Collection of lessons given to struggling spiritual aspirants to enable them surmount the obstacles in Sadhana. Lessons particularly addressed to those who have no faith in God.
Keywords: Self realisation